Social Structures Of Civil Society And Their Features - Gulnoza Karimova (Periodica Journal, 2025)
As a result of the development of society, the foundation of a legal state, the activation of the participation of citizens in self-government and sociopolitical processes, the transition to a market economy, the decentralization of the system of state authorities, conditions are created for the formation of civil society. As civil society develops, the social structures are also improved,its new functions appear. In the context of civil society, it is important to have visions of categories related to it in the analysis of knowledge about the social structure of classification into social structures.
Keywords: structure; society; economic